Application of time reversal technique in shallow water environment - Jastrzębski, Sławomir (Archives of Acoustics, 2007)
Underwater acoustic communications in shallow water environment is a challenging problem due to the intersymbol interference caused by time-varying dispersive multipath channel. The paper describes this effect and the passive time reversal technique and its spatial and temporal focal properties to reduce channel fading and intersymbol interference which causes severe distortions of received communication signals. Recently time reversal technique is a method introduced to the underwater acoustic communication. In a significant multipath environment the time reversal process offers unique opportunity for solving the multipath problem and recovering the original signal at the focus. Communication systems can be divided into incoherent or coherent modulation. In this article coherent underwater acoustic communication method was presented by using passive phase conjugation and 16QAM (quadrature amplitude modulation) as a modulation method. Presented results confirm the utility of the passive phase conjugation in shallow water environment to underwater communications.